Application of the Five-Finger Hypnosis Relaxation Technique in Nursing Care for Hypertensive Patients - Arlies Zenitha Victoria; Davina Rahma Dania Putri Rosiany; Dela Ayu Kurniawati; Desika Indrawati; Desita Triana Adila; May Wulansari (PROFESSIONAL HEALTH JOURNAL, 2026)
Hypertension is often referred to as the "silent killer" because it frequently shows no symptoms. In Indonesia, hypertension continues to rise year after year, with the incidence in 2018 reaching 658,201 cases (34.11%). The causes of hypertension are closely related to age and gender factors. Therefore, non-pharmacological nursing interventions are needed to address this, such as the five-finger hypnosis technique. Five-finger hypnosis involves focusing the mind on images or memories created while touching each of the five fingers in sequence, all in a relaxed state. This study aims to analyze the application of five-finger hypnosis in nursing care for hypertensive patients. The research method used is a case study with the implementation of the five-finger hypnosis nursing intervention. The respondents in this study consisted of five participants diagnosed with hypertension. The patients were taught the five-finger hypnosis technique for approximately 15 minutes. The results showed a decrease in blood pressure after the five-finger hypnosis therapy, with the five respondents (100%) showing an average systolic blood pressure of 146 mmHg, diastolic blood pressure of 91.6 mmHg, and mean arterial pressure (MAP) of 109.74 mmHg. It can be concluded that the five-finger hypnosis therapy is effective in reducing the blood pressure of hypertensive patients. Future researchers are encouraged to extend the duration of five-finger hypnosis therapy for hypertensive patients to achieve a more significant reduction in blood pressure.